Processing on the sanitary quality of seeds of Panicum maximum cv. ‘Tanzânia’ - Lilian F. Melo; Givanildo Z. da Silva; Rita C. Panizzi; Cibele C. Martins (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The aim of this study was to evaluate the sanitary quality of seeds of Panicum maximum cv. ‘Tanzânia’, following the several phases of the seed processing process. Seeds were sampled before processing and after leaving the air and screen machine (upper and intermediary screens and bottom); first gravity table (drift, upper and intermediate spouts); second gravity table (upper, intermediate, and lower spouts), and treating machine for dyeing the seeds. The sanitary analyses were conducted according to the filter paper method, with and without superficial disinfestation of the seeds, which were incubated at a temperature of 20 ± 2 °C with photoperiod of 12 h for seven days. Some seed processing steps may reduce the incidence of seeds of P. maximum cv. ‘Tanzania’ contaminated with Phoma sp. and Helminthosporium sp. In general, the processing can increase the incidence of seeds contaminated with Cladosporium sp. and Cercospora sp. The fungi Phoma sp., Helminthosporium sp., Penicillium sp., Cladosporium sp. and Cercospora sp. are found inside and outside the seeds and can be disseminated by the processing machines.